(This is from baby Rudin 5.2)

Suppose $f'(x) > 0$ in ($a, b$). Prove that $f$ is strictly increasing in ($a, b$), and let $g$ be its inverse function.

Prove that $g$ is differentiable, and that $g'(f(x)) = \frac{1}{f′(x)} \; \; \; (a < x < b)$

Here's an answer I found online:

Let $g : f(a, b) → (a, b) $ be the inverse function of $f$, i.e., $ g(f(x)) = x $ for all $x ∈ (a, b)$.

We now show that $g′(y) = lim_{z→y} \frac {g(z) − g(y)}{z − y}$ exists for all $y ∈ f(a, b)$.

Put $y = f(x)$ and $z = f(t)$, where $x, t ∈ (a, b)$, then since $f$ is continuous (by Theorem 5.2), so is $g$ (by Theorem 4.17), and $z → y$ implies $t → x$.

It follows that $$lim_{z→y} \frac{g(z) − g(y)}{z − y} =$$ $$lim_{t→x}\frac{g(f(t)) − g(f(x))}{f(t) − f(x)}=$$ $$ lim_{t→x}\frac{t − x}{f(t) − f(x)} =$$ $$ lim_{t→x}\frac{1}{\frac{f(t) − f(x)}{t − x}} =$$ $$\frac{1}{f′(x)}$$


Why it is necessary to for g to be continuous? The only step that uses continuity is the changing of the limit values ( $z → y$ implies $t → x$), but that comes from $f$ I think?

Thanks in advance!

  • $\begingroup$ $g$ must be continuous at $y = f(x)$ so that $\lim_{y \rightarrow z} g(z) = g(y) = g(f(x)) = x$. We really need to be able to plug in $x$ into the function $f^{-1}(x)$. $\endgroup$ – D.B. Apr 7 '19 at 15:30
  • $\begingroup$ When we g(y) = g(f(x)), aren't we just plugging values into g? (since we defined y = f(x)). I don't see why the limit is involved to get from g(z)-g(y) to g(f(t)) - g(f(x)) $\endgroup$ – Jess Apr 7 '19 at 15:53

You do not need to assume that the inverse function $g\colon f([a,b])\to [a,b]$ is continuous because that actually does come for free. To see this, it suffices to show that if $U\subset [a,b]$ is an relatively open interval, then $g^{-1}(U)$ is open in $f([a,b])$. Now, $g^{-1}(U) = f(U)$, and since $f$ is strictly increasing, the image of a relatively open interval in $[a,b]$ under $f$ is another relatively open interval in $f([a,b])$.


In fact, we do need continuity of $g$.

If only g is continuous, then $z→y $ implies $f(z)→f(y) $. But this is unhelpful, since we want $t→x $.

Recall the only thing we know is that $y = f(x)$ and $z = f(t)$.

From this, we know $$g(z) = g( f(t)) = t$$ (since $g$ and $f$ are inverses).

Similarly: $$g(y) = g( f(x)) = x.$$

Now, suppose $g$ is continuous.

Then $z→y $ implies $g(z)→g(y) $. (def of continuity).

It follows immediately that $t→x $.


In some sense you are right that the change of limit values comes from the properties $f$. However, proving this is harder than just using a known result that the inverse function of $f$ is continuous. But let's do it just for completeness.

What we want to show is that, given $f(t) \to f(x)$ as $t \to x_0$ for some $x_0 \in (a,b)$, it must be the case that $x_0 = x$. We argue by contradiction. Suppose $x_0 \neq x$. By the continuity of $f$, we have that $f(x_0) = f(x)$. Assume, without loss of generality, that $x < x_0$. Then the mean value theorem tells us there exists $c \in (x,x_0) \subset (a,b)$ such that $$f'(c) = \frac{f(x_0) - f(x)}{x_0 - x} = \frac{0}{x_0-x}=0.$$ But this contradicts that $f'(x) > 0$ for all $x \in (a,b)$. Thus, $x = x_0$ must hold. Hence, we have shown that for any $t,x \in (a,b)$, $f(t) \to f(x)$ implies that $t \to x$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.